A coated fluoropolymer, a method for its preparation and a polymer composition

CN116948185BActive Publication Date: 2026-10-30FUJIAN XINAN TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310900021.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2026-10-30
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

四氟乙烯聚合物作为添加助剂已被用来作为聚合物材料中的抗滴落剂,但是,四氟乙烯聚合物作为阻燃聚合物组合物的抗滴落剂存在一个问题,单独使用无法满足阻燃要求,其通常需要与一种或多种阻燃剂复配使用

Benefits of technology

[0027]本发明提供了一种包覆型氟聚合物,其特征在于,包括表面被含硅和硫的共聚物完全或部分包覆的氟聚合物,所述包覆型氟聚合物由乳液-水解缩合聚合法制备得到,包括以下步骤:A)以水或水-有机溶剂为分散介质,以硅化合物a和含不饱和基磺酸盐单体为共聚单体,在引发剂的存在下,经乳液聚合,得到共聚乳液c;B)以水或水-有机溶剂为分散介质,使氟聚合物、碱性化合物、共聚乳液c以及可选的硅化合物b发生水解-缩合反应,得到反应乳液;C)将所述反应乳液固液分离并干燥,得到包覆型氟聚合物颗粒;所述含硅和硫的共聚物为具有交联结构的聚合物;所述包覆型氟聚合物中氟聚合物与含硅和硫的共聚物的质量比为95:5~5:95;所述包覆型氟聚合物中硫元素的质量分数为0.1-10%。本发明利用了磺酸盐对PC的高效阻燃、有机硅化合物的协效阻燃性能及抗滴落剂的抗滴落性能,使用磺酸盐结构和有机硅包覆PTFE,将3种物质制成一个产品,而又不影响自身的阻燃性,特别是抗滴落剂经过包覆后的阻燃分散性能不受影响,能够实现更高级别的阻燃。此外,本发明利用不饱和基团的乳液聚合,得到分散性好的包覆型防滴落剂,有效避免抗滴落剂凝聚,结团等无法使用,或使用时制品缺陷严重的现象发生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004351429620000151
    Figure BDA0004351429620000151
Patent Text Reader

Abstract

The application provides a coated fluoropolymer, comprising a fluoropolymer which is completely or partially coated by a copolymer containing silicon and sulfur, wherein the coated fluoropolymer is prepared by an emulsion-hydrolysis condensation polymerization method, comprising the following steps: A) using water or a water-organic solvent as a dispersion medium, using a silicon compound a and an unsaturated group-containing sulfonate monomer as a comonomer, and performing emulsion polymerization in the presence of an initiator to obtain a copolymer emulsion c; B) using water or a water-organic solvent as a dispersion medium, and performing a hydrolysis-condensation reaction of a fluoropolymer, an alkaline compound, the copolymer emulsion c and an optional silicon compound b to obtain a reaction emulsion; and C) performing solid-liquid separation and drying on the reaction emulsion to obtain coated fluoropolymer particles. The application uses a sulfonate structure and organic silicon to coat PTFE, and can achieve higher levels of flame retardation. The application also provides a preparation method of the coated fluoropolymer and a polymer composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer processing technology, and particularly relates to a coated fluoropolymer, its preparation method and polymer composition. Background Technology

[0002] Currently, fluoropolymers, represented by tetrafluoroethylene (TEF) polymers, generally possess excellent high and low temperature resistance, non-stick properties, corrosion resistance, and flame retardant properties, and have been widely used in chemical, textile, electronics, medical, and machinery industries. TEF polymers have been used as additives as anti-dripping agents in polymer materials. However, there is a problem with using TEF polymers as anti-dripping agents in flame-retardant polymer compositions: they cannot meet flame retardant requirements when used alone, and they usually need to be used in combination with one or more flame retardants.

[0003] Patent EP-AD 166187 uses a co-precipitation method to obtain acrylonitrile-butadiene-styrene modified polytetrafluoroethylene powder. Its disadvantages are high self-adhesion, poor free flow of powder when the polytetrafluoroethylene content is high, and need to be compounded with other flame retardants to achieve flame retardant effect, and the appearance of the product is defective.

[0004] Patent CN1125096C describes a method for preparing coated tetrafluoroethylene polymer particles using free radical emulsion polymerization. The coating material is selected from polystyrene, polyα-methylstyrene, styrene-acrylonitrile copolymer, α-methylstyrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, and mixtures thereof. This coating material lacks flame retardancy, and its flame retardant properties even decrease at higher addition levels. Patents CN102286157A, CN103849092A, CN112876791A, and their related divisional patents employ different preparation methods to obtain fluoropolymer particles coated with different organosilicon polymers, but these require compounding with other flame retardants. Summary of the Invention

[0005] The purpose of this invention is to provide a coated fluoropolymer, its preparation method and polymer composition. The fluoropolymer prepared by the preparation method of this invention has both anti-dripping and flame-retardant properties, and does not cause a decrease in the mechanical properties of the polymer composition.

[0006] This invention provides a coated fluoropolymer, comprising a fluoropolymer whose surface is completely or partially coated with a copolymer containing silicon and sulfur, wherein the coated fluoropolymer is prepared by an emulsion-hydrolysis condensation polymerization method, comprising the following steps:

[0007] A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c;

[0008] B) Using water or a water-organic solvent as the dispersion medium, the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b undergo a hydrolysis-condensation reaction to obtain a reactive emulsion;

[0009] C) The reaction emulsion is separated into solid and liquid phases and dried to obtain a coated fluoropolymer;

[0010] The silicon- and sulfur-containing copolymer is a polymer with a cross-linked structure;

[0011] The mass ratio of the fluoropolymer to the silicon- and sulfur-containing copolymer in the coated fluoropolymer is 95:5 to 5:95.

[0012] The mass fraction of sulfur in the coated fluoropolymer is 0.1% to 10%.

[0013] Preferably, the silicon compound a includes one or more of the following: compounds containing unsaturated groups and having hydrolyzable groups attached to silicon atoms, their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof;

[0014] The silicon compound b includes one or more of the following: compounds having hydrolyzable groups attached to silicon atoms, their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof.

[0015] Preferably, at least one of the silicon compound a and silicon compound b contains a trifunctional silicon compound and / or a tetrafunctional silicon compound.

[0016] Preferably, the fluoropolymer is selected from homopolymers, copolymers, or mixtures thereof comprising repeating units derived from one or more fluorinated α-olefin monomers.

[0017] Preferably, the fluoropolymer is a fibrillated fluoropolymer.

[0018] Preferably, the unsaturated sulfonate monomer comprises one or more of sodium styrene sulfonate, potassium styrene sulfonate, sodium allyl sulfonate, potassium allyl sulfonate, sodium vinyl sulfonate, potassium vinyl sulfonate, sodium methyl allyl sulfonate, potassium methyl allyl sulfonate, sodium 3-allyloxy-2-hydroxy-1-propanesulfonate, potassium 3-allyloxy-2-hydroxy-1-propanesulfonate, sodium 2-acrylamido-2-methylpropanesulfonate, and potassium 2-acrylamido-2-methylpropanesulfonate.

[0019] Preferably, the emulsion polymerization temperature in step A) is 60–90°C, and the emulsion polymerization time in step A) is 1–10 hours.

[0020] Preferably, the temperature of the hydrolysis-condensation reaction in step B) is 0 to 90°C, and the time of the hydrolysis-condensation reaction in step B) is 0.1 to 10 hours.

[0021] This invention provides a method for preparing a coated fluoropolymer, comprising the following steps:

[0022] A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c;

[0023] B) Using water or a water-organic solvent as the dispersion medium, the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b undergo a hydrolysis-condensation reaction to obtain a reactive emulsion;

[0024] C) The reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles.

[0025] This invention provides a polymer composition comprising a polymer matrix and a coated fluoropolymer dispersed in the polymer matrix;

[0026] The coated fluoropolymer is the coated fluoropolymer described above.

[0027] This invention provides a coated fluoropolymer, characterized in that it comprises a fluoropolymer whose surface is completely or partially coated with a copolymer containing silicon and sulfur. The coated fluoropolymer is prepared by an emulsion-hydrolysis-condensation polymerization method, comprising the following steps: A) using water or a water-organic solvent as a dispersion medium, and using a silicon compound a and an unsaturated sulfonate monomer as comonomers, in the presence of an initiator, an emulsion polymerization is carried out to obtain a copolymer emulsion c; B) using water or a water-organic solvent as a dispersion medium, the fluoropolymer, an alkaline compound, copolymer emulsion c, and optionally a silicon compound b undergo a hydrolysis-condensation reaction to obtain a reaction emulsion; C) the reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles; the copolymer containing silicon and sulfur is a polymer with a cross-linked structure; the mass ratio of the fluoropolymer to the copolymer containing silicon and sulfur in the coated fluoropolymer is 95:5 to 5:95; the mass fraction of sulfur in the coated fluoropolymer is 0.1-10%. This invention utilizes the highly efficient flame retardancy of sulfonates on PC, the synergistic flame retardant properties of organosilicon compounds, and the anti-dripping properties of anti-dripping agents. By using a sulfonate structure and organosilicon-coated PTFE, these three substances are formulated into a single product without compromising the product's inherent flame retardancy. In particular, the flame-retardant dispersion properties of the anti-dripping agent remain unaffected after coating, achieving a higher level of flame retardancy. Furthermore, this invention employs emulsion polymerization of unsaturated groups to obtain a well-dispersible coated anti-dripping agent, effectively preventing the anti-dripping agent from agglomerating, clumping, or becoming unusable, or resulting in severely defective products. Detailed Implementation

[0028] This invention provides a coated fluoropolymer, characterized in that it comprises a fluoropolymer whose surface is completely or partially coated with a copolymer containing silicon and sulfur, wherein the coated fluoropolymer is prepared by an emulsion-hydrolysis condensation polymerization method, comprising the following steps:

[0029] A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c;

[0030] B) Using water or a water-organic solvent as the dispersion medium, the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b undergo a hydrolysis-condensation reaction to obtain a reactive emulsion;

[0031] C) The reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles;

[0032] The silicon- and sulfur-containing copolymer is a polymer with a cross-linked structure;

[0033] The mass ratio of the fluoropolymer to the silicon- and sulfur-containing copolymer in the coated fluoropolymer is 95:5 to 5:95.

[0034] The mass fraction of sulfur in the coated fluoropolymer is 0.1% to 10%.

[0035] In this invention, the coated fluoropolymer is preferably a free-flowing particle, and the average particle size of the coated fluoropolymer is preferably 0.01 to 1000 μm.

[0036] In this invention, the fluoropolymer is preferably a homopolymer and / or copolymer, the fluoropolymer comprising repeating units derived from one or more fluorinated α-olefin monomers.

[0037] The fluorinated α-olefin monomer is preferably an α-olefin monomer containing at least one fluorine atom substituent, such as fluorinated vinyl groups like CF2=CF2, CHF=CF2, CH2=CF2, CH2=CHF, CClF=CF2, CH2=CClF, and CCl2=CClF, and fluorinated propylene groups like CF3CF=CF2, CF3CF=CHF, CF3CH=CF2, and CF3CH=CH2. The fluoropolymers and methods for preparing these fluoropolymers are well known, see patents US3671487, US3723373, and US3383092.

[0038] In this invention, the homopolymer of fluorinated α-olefins is preferably one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride, polyhexafluoropropylene, and polychlorotrifluoroethylene; the copolymer of fluorinated α-olefins contains repeating units derived from two or more fluorinated α-olefin copolymers, such as tetrafluoroethylene-hexafluoropropylene copolymer and tetrafluoroethylene-vinylidene fluoride copolymer; and it contains repeating units derived from one or more fluorinated monomers and repeating units derived from one or more non-fluorinated olefin unsaturated monomers capable of copolymerizing with the fluorinated monomers, such as tetrafluoroethylene-ethylene copolymer and tetrafluoroethylene-ethylene-propylene copolymer. In this invention, the non-fluorinated olefin unsaturated monomers include α-olefin monomers such as ethylene and propylene, such as (meth)acrylic acid monomers such as methyl methacrylate and butyl acrylate, such as vinyl ether monomers such as cyclohexyl vinyl ether and ethyl vinyl ether, and such vinyl ester monomers such as vinyl acetate and vinyl tert-carbonate.

[0039] In this invention, the fluoropolymer may or may not be fibrillated, but fibrillated is preferred.

[0040] In this invention, the fluoropolymer is preferably a tetrafluoroethylene polymer. The tetrafluoroethylene polymers that can be used include: polytetrafluoroethylene, tetrafluoroethylene-vinylidene fluoride copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-vinyl fluoride copolymer, and copolymers of tetrafluoroethylene with other copolymerizable olefinic unsaturated monomers. These polymers are well known in the art.

[0041] In the present invention, the fluoropolymer is further preferably polytetrafluoroethylene (PTFE).

[0042] In this invention, the silicon- and sulfur-containing copolymer is a polymer with a cross-linked structure. In the silicon- and sulfur-containing copolymer, sulfur exists in the form of a sulfonate. The mass fraction of sulfur in the coated fluoropolymer particles is preferably 0.01 to 10%, more preferably 0.1 to 8%, such as 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, preferably within the range of values ​​above, which may be the upper or lower limits.

[0043] In this invention, the silicon- and sulfur-containing copolymer contains a main chain of Si-O segments and a branched structure of RSiO. 3 / 2 And / or SiO2 structural units, where each R is an independent monovalent organic group.

[0044] In this invention, the coated fluoropolymer is prepared by an emulsion-hydrolysis condensation polymerization method, comprising the following steps:

[0045] A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c;

[0046] B) Using water or a water-organic solvent as the dispersion medium, the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b undergo a hydrolysis-condensation reaction to obtain a reactive emulsion;

[0047] C) The reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles.

[0048] In this invention, the silicon compound a is selected from compounds containing unsaturated groups and having hydrolyzable groups attached to silicon atoms, their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof. The hydrolyzable groups attached to silicon atoms are preferably one or more of alkoxy, acyloxy, silanyl, silazyl, ketoxime, and silane groups, more preferably alkoxy, silanyl, or silane groups having 1 to 6 carbon atoms, further preferably alkoxy, and most preferably methoxy or ethoxy.

[0049] Specifically, in this invention, the silicon compound a includes one or more of vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, tetramethyldivinyldisiloxane, 3-(methacryloyloxy)propyltrichlorosilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, and 3-(methacryloyloxy)propylmethyldimethoxysilane, preferably vinyltrimethoxysilane, vinyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, and their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof, further preferably vinyltrimethoxysilane and / or vinyltriethoxysilane, and most preferably vinyltrimethoxysilane.

[0050] The silicon compound b preferably includes one or more of the following: compounds having hydrolyzable groups attached to silicon atoms, their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof. The hydrolyzable groups attached to silicon atoms include alkoxy, acyloxy, silanyl, silazyl, ketoxime, silanyl halide, etc., preferably alkoxy, silanyl, or silanyl halide having 1 to 6 carbon atoms, further preferably alkoxy, and most preferably methoxy and / or ethoxy.

[0051] Specifically, in this invention, the silicon compound b includes methyltrichlorosilane, trimethylchlorosilane, silicon tetrachloride, chloropropyltrichlorosilane, chloropropyltrimethoxysilane, triethylchlorosilane, n-dodecyltrichlorosilane, octylmethyldichlorosilane, vinyltrichlorosilane, phenyltrichlorosilane, (3,3,3-trifluoropropyl)methyldichlorosilane and similar chlorosilanes, tetramethoxysilane, tetraethoxysilane and similar silicates, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane, methylphenyldimethoxysilane and similar compounds. Alkoxysilanes, methyltributanone oxime silanes, vinyltributanone oxime silanes and similar ketoxime silanes, methyltriacetoxysilanes, vinyltriacetoxysilanes and similar acyloxysilanes, trimethoxysilanes, trimethylsilanes and similar Si-H silanes, trimethylsilane-terminated polymethylhydrosiloxanes, trimethylsilane-terminated dimethylsiloxane-methylhydrosiloxane copolymers and similar Si-H siloxanes, hexamethyldisilazanes and similar silazanes, 3-aminopropyltrimethoxysilanes, bis(trimethoxysilylpropyl)amine, 3-aminopropylmethyldiethoxysilanes, 3-(2-aminoethylamino)propyltrimethoxysilanes, diethylenetrimethoxysilanes Aminopropyltrimethoxysilane, diethylenetriaminopropylmethyldimethoxysilane, anilinemethyltrimethoxysilane, cyclohexylaminopropyltrimethoxysilane, diethylaminomethyltriethoxysilane and similar aminosilanes, mercaptopropyltrimethoxysilane, mercaptopropylmethyldimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, bis(triethoxysilylpropyl)disulfide and similar sulfur-containing silanes, 3-thiocyanopropyltriethoxysilane and similar thiocyanosilanes, 3-ureapropyltrimethoxysilane and similar ureosilanes, 3-isocyanopropyltrimethoxysilane and similar isocyanosilanes, 3-glycidyl etheroxypropyltrimethoxysilane, 3 - Glycidyl etheroxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and similar epoxysilanes, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, 3-acryloyloxypropyltrimethoxysilane and similar acryloxysilanes, phenyltriethoxysilane, diphenyldimethoxysilane, methylphenyldiethoxysilane and similar phenylsilanes, vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmethoxysilane and similar vinylsilanes, and their hydrolysis products, partially hydrolyzed-condensed products and mixtures thereof.

[0052] In this invention, all components of silicon compound a and silicon compound b include a tetrafunctional silicon compound SiX4(Q), a trifunctional silicon compound RSiX3(T), a difunctional silicon compound R2SiX2(D), and a monofunctional silicon compound R3SiX(M), with the following proportions:

[0053] SiX4(Q): 0–20% mol,

[0054] RSiX3(T): 50–100% mol

[0055] R2SiX2(D): 0–10% mol,

[0056] R3SiX(M): 0–10% mol,

[0057] That is, of the two silicon compounds, a and b, at least one contains a trifunctional silicon compound and / or a tetrafunctional silicon compound.

[0058] The total mass percentage of SiX4(Q) and RSiX3(T) silicon compounds is 70-100% mol, each R is an independent monovalent organic group, and each X is an independent monovalent hydrolyzable group connected to a silicon atom.

[0059] Preferably, each R is independently a monovalent hydrocarbon group having 1 to 30 carbon atoms, either substituted or unsubstituted, for example, a straight-chain, branched, or cyclic alkyl group having 1 to 12 carbon atoms, preferably 1 to 8 carbon atoms, more preferably 1 to 6 carbon atoms; a straight-chain or branched alkenyl group having 2 to 10 carbon atoms, preferably 2 to 8 carbon atoms, more preferably 2 to 6 carbon atoms; an aryl group optionally substituted with the above-mentioned alkyl group, such as phenyl or naphthyl; or an alkyl group optionally substituted with an aryl group, such as phenyl; wherein some or all of the hydrogen atoms bonded to the carbon atoms of these groups are halogenated. The atoms (fluorine, chlorine, bromine, iodine) and / or alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl and phenethyl; alkenyl groups such as vinyl, allyl, propenyl, butenyl, hexenyl, and heptenyl; and cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl. Preferably, 60% mol or more of R is methyl, phenyl, or vinyl. Preferably, each X represents a halogen atom such as chlorine, or a hydrolyzable group such as an alkoxy or acyloxy group, and more preferably an alkoxy group such as methoxy or ethoxy.

[0060] In this invention, it has been found that when the silicon compound a used in step (A) is a trifunctional silicon compound, silicon compound b can be omitted in step (B) and still have a good coating effect. However, if the silicon compound a used in step (A) is a difunctional silicon compound and / or a monofunctional silicon compound, then silicon compound b must be used, and silicon compound b must contain a tetrafunctional silicon compound SiX4(Q) and / or a trifunctional silicon compound RSiX3(T). Otherwise, there will be no coating effect, and a silicon-containing and sulfur-containing copolymer with a cross-linked structure cannot be obtained. In this invention, it is further preferred that silicon compound b contains a trifunctional silicon compound RSiX3(T), and each R and each X is the same as described above.

[0061] In this invention, the unsaturated sulfonate monomer includes one or more of sodium styrene sulfonate, potassium styrene sulfonate, sodium allyl sulfonate, potassium allyl sulfonate, sodium vinyl sulfonate, potassium vinyl sulfonate, sodium methyl allyl sulfonate, potassium methyl allyl sulfonate, sodium 3-allyloxy-2-hydroxy-1-propanesulfonate, potassium 3-allyloxy-2-hydroxy-1-propanesulfonate, sodium 2-acrylamido-2-methylpropanesulfonate, and potassium 2-acrylamido-2-methylpropanesulfonate.

[0062] In this invention, the mass ratio of the silicon compound a to the unsaturated sulfonate monomer is preferably (0.1-20):1, more preferably (5-15):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, and preferably a range of values ​​with any of the above values ​​as the upper or lower limit.

[0063] In this invention, the dispersion medium used to prepare the copolymer emulsion c is water or a water-organic solvent, preferably water, with no particular restrictions on the type of water. Sometimes, to control the stability of the reaction system, an electrolyte may be selectively added, with no restrictions on the type of electrolyte, such as sodium chloride, magnesium sulfate, calcium chloride, etc. However, this invention preferably does not add an electrolyte.

[0064] In this invention, the initiator is preferably sodium persulfate, potassium persulfate, ammonium persulfate, benzoyl peroxide, azobisisobutyronitrile, redox initiator systems such as sodium persulfate-sodium bisulfite, and mixtures thereof.

[0065] In this invention, the mass of the initiator is preferably 0.01 to 10% of the total mass of silicon compound a and unsaturated sulfonate monomer, more preferably 1 to 8%, such as 0.01%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, preferably a range of values ​​with any of the above values ​​as the upper or lower limit.

[0066] In this invention, the emulsion polymerization temperature is preferably 60-90°C, more preferably 70-80°C, and the emulsion polymerization time is preferably 1-10 hours, more preferably 3-8 hours, and most preferably 5-6 hours.

[0067] After obtaining copolymer emulsion c, the present invention uses water or a water-organic solvent as a dispersion medium to cause hydrolysis-condensation reaction of fluoropolymer, basic compound, copolymer emulsion c and optional silicon compound b to obtain reaction emulsion.

[0068] In this invention, the type of fluoropolymer is the same as that described above, and will not be repeated here. The fluoropolymer used in this invention is not limited in its form of use; it can be a single type of fluoropolymer particles and its dispersion, or a blend of two or more fluoropolymers. The single type of fluoropolymer particles are known fluoropolymers, and its dispersion can be a commercially available dispersion with a certain solid content, or a fluoropolymer dispersion obtained by aqueous polymerization. This polymer dispersion does not require a concentration step, such as concentration to a solid content of 30% or 60%. The fluoropolymer blend particles or its dispersion can be obtained by mixing single type of fluoropolymer fine powder particles or its dispersion. The fluoropolymer is preferably a blend of fluoropolymer fine powder particles and its dispersion, further preferably a single type of fluoropolymer particles and its dispersion, more preferably polytetrafluoroethylene (PTFE) particles and its dispersion, and most preferably PTFE particles and its dispersion capable of fibrillation. Those skilled in the art can easily determine the morphology, particle size, and molecular weight of the fluoropolymer used according to the final requirements.

[0069] In this invention, the alkaline compound is preferably a water-soluble alkaline compound that alkalizes the water or water-organic solvent dispersion medium, such as alkali metal hydroxides like potassium hydroxide and sodium hydroxide, alkaline earth metal hydroxides like calcium hydroxide and magnesium hydroxide, alkali metal carbonates like potassium carbonate and sodium carbonate, amine compounds like ethylamine, propylamine, butylamine, dimethylamine, trimethylamine, and triethylamine, silanols, quaternary ammonium bases, quaternary phosphorus bases, silanol quaternary ammonium salts, silanol quaternary phosphorus salts, and one or more of alkali metal organometallic compounds and ammonia compounds. Ammonia compounds are preferred in this invention because they are water-soluble, have high catalytic activity, are volatile, and are easily removed from the product. Ammonia water is further preferred, and most preferably ammonia water containing 25-30% ammonia by mass. This invention does not have a particular limitation on the pH value of the dispersion medium after alkalization with the alkaline compound, but 9-14 is preferred, and 10-12 is more preferred.

[0070] In this invention, the amounts of the alkaline compound, fluoropolymer, and silicon compound used are all conventional amounts in the art, and will not be described in detail here.

[0071] In this invention, the dispersion medium used for the hydrolysis-condensation reaction is water or a water-organic solvent, with water being preferred, and there are no particular restrictions on the type of water. Sometimes, to control the stability of the reaction system, an electrolyte may be selectively added, with no restrictions on the type of electrolyte, such as sodium chloride, magnesium sulfate, calcium chloride, etc. However, this invention preferably does not add an electrolyte.

[0072] In this invention, the temperature of the hydrolysis-condensation reaction is preferably 0-90°C, more preferably 10-80°C, and most preferably 50-70°C; the time of the hydrolysis-condensation reaction is preferably 0.1-10 hours, more preferably 1-8 hours, and most preferably 2-5 hours.

[0073] The resulting reaction emulsion is a coated fluoropolymer emulsion. After solid-liquid separation and drying, the coated fluoropolymer is obtained.

[0074] In this invention, the solid-liquid separation can be achieved by removing water, organic solvents, etc., from the emulsion or dispersion to obtain coated fluoropolymer particles. Alternatively, it can be achieved by heating, centrifugation, filtration, decantation, or other methods, followed by washing as needed. The resulting polymer blend powder particles are then obtained by thermal drying under normal or reduced pressure, spraying the dispersion into a hot air stream, or using a heating medium. If the fluoropolymer used is protofibrous, the dried coated fluoropolymer particles are not suitable for forced pulverization methods such as grinding or air jet milling, as this would lead to premature fibrosis of the fluoropolymer. The above-mentioned solid-liquid separation and drying methods are commonly used by those skilled in the art, and will not be elaborated further in this invention.

[0075] This invention also provides a method for preparing a coated fluoropolymer, comprising the following steps:

[0076] A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c;

[0077] B) Using water or a water-organic solvent as the dispersion medium, the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b undergo a hydrolysis-condensation reaction to obtain a reactive emulsion;

[0078] C) The reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles.

[0079] This invention targets fluoropolymers that simultaneously incorporate sulfonate structures and silicon compounds. It employs a method of first performing free radical polymerization of the silicon compound and the sulfonate monomer, followed by hydrolysis and condensation of the free radical polymerization product in the presence of the fluoropolymer and an alkaline catalyst, successfully introducing sulfonate structures into the coating structure on the surface of the fluoropolymer. In this invention, the raw materials, preparation steps, and process parameters used in the preparation of the coated fluoropolymer are consistent with those described above, and will not be repeated here.

[0080] The present invention also provides a polymer composition comprising a polymer matrix and a coated fluoropolymer dispersed in the polymer matrix; wherein the coated fluoropolymer is the coated fluoropolymer described above.

[0081] In this invention, the polymer matrix is ​​preferably a vinyl polymer such as polyvinyl chloride, polyvinyl alcohol, and polyvinyl acetate; a polyolefin such as polyethylene and polypropylene; a polyalkylene terephthalate such as polybutylene terephthalate and polyethylene terephthalate; a polyacrylate such as polymethyl acrylate; a polymethacrylate such as polymethyl methacrylate; a polyphenylene ether; a polysulfone; a polycarbonate; a polystyrene, especially high-impact polystyrene; a polyamide such as nylon 6 and nylon 66; a polyimide; a styrene-acrylonitrile copolymer; a styrene-butadiene copolymer; an acrylonitrile-butadiene-styrene copolymer; an acrylonitrile-butadiene-styrene copolymer / polycarbonate blend; a polystyrene / polyphenylene ether blend; a thermoplastic polyester / polycarbonate blend such as a butylene terephthalate / polycarbonate blend; silicone rubber; and mixtures thereof, further preferably polycarbonate, copolymers thereof, and mixtures thereof, with polycarbonate being the most preferred.

[0082] The polymer compositions of the present invention may also contain flame retardants. There are no particular limitations on the flame retardants used; any known flame retardant system for polymer compositions can be used. The flame retardants used in the polymer compositions may be used alone or in combination.

[0083] According to the present invention, any conventional additives, such as pigments, UV stabilizers, antioxidants, heat stabilizers, reinforcing fillers, chain extenders, colorants, toughening agents, etc., can be added to the polymer composition.

[0084] The preparation method of the polymer composition can be any known method of mixing the components. Typically, it involves two different mixing steps: premixing and melt mixing, and these methods are well known.

[0085] In this field, fluoropolymers have been used as anti-dripping agents, abrasion resistant agents, etc. in flame-retardant polymer compositions. The coated fluoropolymer particles of the present invention have proven to be particularly effective in increasing the flame retardancy of polymer compositions, especially the flame retardancy of polycarbonate.

[0086] The polymer composition of the present invention exhibits significantly improved flame retardant properties without affecting dispersibility or mechanical properties.

[0087] In this invention, the mass fraction of the coated fluoropolymer in the fluoropolymer composition is preferably 0.01 to 50%, more preferably 0.01 to 26%, even more preferably 0.1 to 8%, and most preferably 0.1 to 2%.

[0088] This invention provides a coated fluoropolymer, characterized in that it comprises a fluoropolymer whose surface is completely or partially coated with a copolymer containing silicon and sulfur. The coated fluoropolymer is prepared by an emulsion-hydrolysis-condensation polymerization method, comprising the following steps: A) using water or a water-organic solvent as a dispersion medium, and using a silicon compound a and an unsaturated sulfonate monomer as comonomers, in the presence of an initiator, an emulsion polymerization is carried out to obtain a copolymer emulsion c; B) using water or a water-organic solvent as a dispersion medium, the fluoropolymer, an alkaline compound, copolymer emulsion c, and optionally a silicon compound b undergo a hydrolysis-condensation reaction to obtain a reaction emulsion; C) the reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles; the copolymer containing silicon and sulfur is a polymer with a cross-linked structure; the mass ratio of the fluoropolymer to the copolymer containing silicon and sulfur in the coated fluoropolymer is 95:5 to 5:95; and the mass fraction of sulfur in the coated fluoropolymer is 0.1% to 10%. This invention utilizes the highly efficient flame retardancy of sulfonates on PC, the synergistic flame retardant properties of organosilicon compounds, and the anti-dripping properties of anti-dripping agents. By using a sulfonate structure and organosilicon-coated PTFE, these three substances are formulated into a single product without compromising the product's inherent flame retardancy. In particular, the flame-retardant dispersion properties of the anti-dripping agent remain unaffected after coating, achieving a higher level of flame retardancy. Furthermore, this invention employs emulsion polymerization of unsaturated groups to obtain a well-dispersible coated anti-dripping agent, effectively preventing the anti-dripping agent from agglomerating, clumping, or becoming unusable, or resulting in severely defective products.

[0089] To further illustrate the present invention, the following detailed description of a coated fluoropolymer, its preparation method, and polymer composition provided by the present invention is provided in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0090] Example 1

[0091] (1) Add 200g of water, 5g of sodium p-styrene sulfonate with a moisture content of 10% and 8.28g of methacryloyloxypropyltrimethoxysilane to a 500ml three-necked flask, start stirring and heat to 80℃, then add a pre-prepared solution containing 0.1g of sodium persulfate and 20g of water. After 5h, heat to 90℃ and continue the reaction for 1h to obtain a basically transparent copolymer emulsion c.

[0092] (2) Add 50g of polytetrafluoroethylene (PTFE) dispersion with a solid content of 60% (standard relative gravity SSG is 2.190), 70g of water, and 0.1g of sodium hydroxide to another 500ml three-necked flask, start stirring, and add (1) to obtain copolymer emulsion c at room temperature. Heat to 30℃, and add the pre-prepared mixture containing 34.13g of methyltrimethoxysilane, 1.85g of aminopropyltriethoxysilane and 3.97g of phenyltrimethoxysilane dropwise through a constant pressure dropping funnel within 30min. Then heat to 70℃ and maintain the reaction for 2h before stopping. After vacuum filtration and drying, 59.8g of coated fluoropolymer particles with an average particle size of 160μm, a sulfur content of 1.1% by weight, and a PTFE content of about 50% by weight are obtained.

[0093] Example 2

[0094] (1) Add 150g of water, 5g of sodium allyl sulfonate with a moisture content of 10% and 11.19g of vinyltrimethoxysilane to a 500ml three-necked flask. After stirring and heating to 80℃, a small amount of suspended matter appears in the system. Add a pre-prepared solution containing 0.1g of sodium persulfate and 20g of water. After 5h, heat to 90℃ and continue the reaction for 1h to obtain copolymer emulsion c.

[0095] (2) Add 50g of polytetrafluoroethylene (PTFE) dispersion with a solid content of 60% (standard relative gravity SSG is 2.190), 150g of water, and 0.1g of sodium hydroxide to another 500ml three-necked flask, start stirring, and add (1) to obtain copolymer emulsion c at room temperature. Heat to 30℃, and add the pre-prepared mixture containing 34.13g of methyltrimethoxysilane, 1.85g of aminopropyltriethoxysilane and 3.97g of phenyltrimethoxysilane dropwise through a constant pressure dropping funnel within 30min. Then heat to 70℃, maintain the reaction for 2h and then stop. After vacuum filtration and drying, 59.5g of coated fluoropolymer particles with an average particle size of 96μm, a sulfur content of 1.5% by weight, and a PTFE content of about 50% by weight are obtained.

[0096] Example 3

[0097] (1) Add 320g of water, 5g of sodium allyl sulfonate with a moisture content of 10% and 49.32g of vinyltrimethoxysilane to a 500ml three-necked flask. After stirring and heating to 80℃, a small amount of suspended matter appears in the system. Add a pre-prepared solution containing 0.1g of sodium persulfate and 20g of water. After 5h, heat to 90℃ and continue the reaction for 1h to obtain a copolymer emulsion c containing obvious suspended matter.

[0098] (2) Add 50g of polytetrafluoroethylene (PTFE) dispersion with a solid content of 60% (standard relative gravity SSG is 2.190) and 0.1g of sodium hydroxide to another 500ml three-necked flask, start stirring, add (1) at room temperature to obtain copolymer emulsion c, heat to 70 degrees, maintain the reaction for 2h and then stop. After vacuum filtration and drying, 58.9g of coated fluoropolymer particles with an average particle size of 310μm, a sulfur content of 1.6% by weight and a PTFE content of about 50% by weight are obtained.

[0099] Comparative Example 1

[0100] 800g of water, 4g of OP-10, 20g of 28% ammonia solution, and 100g of a 60% solids polytetrafluoroethylene dispersion (SSG 2.190) were added to a reaction vessel. After stirring at room temperature until homogeneous, 121.6g of methyltrimethoxysilane was added dropwise to the reaction vessel. The addition was completed after about 30 minutes. The viscosity of the system increased and solid suspensions appeared. The mixture was stirred at a constant temperature for another 30 minutes, then the temperature was raised to 50°C and stirred for 2 hours to stop the reaction. After washing and filtering, the mixture was dried in a hot circulating drying oven at 105°C to obtain 120g of a white powder of polymer blend with a water content of less than 0.3% wt and a polytetrafluoroethylene content of about 50% by weight.

[0101] Comparative Example 2

[0102] A drip-resistant polymeric sulfonate flame retardant, comprising the following raw materials in parts by weight:

[0103] Each part of the unsaturated sulfonate is a mixture of sodium styrene sulfonate, sodium vinyl sulfonate, and sodium methyl allyl sulfonate in a weight ratio of 0.8:0.4:0.1. Each part of the unsaturated monomer is a mixture of vinyl ethyl ether, styrene, and acrylonitrile in a weight ratio of 0.8:0.1:0.4. Each part of the initiator is a mixture of ammonium persulfate, potassium persulfate, and a redox system of tert-butyl hydroperoxide-sodium bisulfite in a weight ratio of 0.5:0.8:0.4. Each part of the coagulant is calcium chloride. Each part of the emulsifier is a mixture of fatty acid sulfonyl ester, N-alkyl diethanolamine salt, and alkylphenol polyoxyethylene ether in a weight ratio of 0.8:0.4:0.6.

[0104] This anti-drip polymeric sulfonate flame retardant comprises the following steps:

[0105] 1) According to the weight parts, mix the emulsifier, unsaturated sulfonate, unsaturated monomer and part of deionized water, heat to 40°C and stir at 180 r / min until uniform, to obtain mixture A and keep it warm for later use.

[0106] 2) Add the initiator to the mixture A obtained in step 1), stir and heat to 40°C to carry out free radical reaction for 2 hours to obtain a high molecular weight sulfonate copolymer emulsion for later use;

[0107] 3) Add another portion of deionized water and polytetrafluoroethylene emulsion to the polymer sulfonate copolymer emulsion obtained in step 2), heat to 70°C and stir for 2 hours to obtain mixture B, which is set aside; the mass ratio of deionized water added in step 1) to deionized water added in step 3) is 3:6.

[0108] 4) Add the coagulant to mixture B, stir evenly, heat to 60°C, demulsify for 3 hours, wash the obtained precipitate, dry and pulverize at 100°C to obtain anti-drip polymeric sulfonate flame retardant.

[0109] Comparative Example 3

[0110] (1) Add 320g of water, 5g of sodium allyl sulfonate with a moisture content of 10% and 49.32g of vinyltrimethoxysilane to a 500ml three-necked flask. After stirring and heating to 80℃, a small amount of suspended matter appears in the system. Add a pre-prepared solution containing 0.1g of sodium persulfate and 20g of water. After 5h, heat to 90℃ and continue the reaction for 1h to obtain a copolymer emulsion c containing obvious suspended matter.

[0111] (2) Add 50g of polytetrafluoroethylene (SSG standard relative gravity is 2.190) dispersion with a solid content of 60% to another 500ml three-necked flask, start stirring, add (1) to obtain copolymer emulsion c and coagulant calcium chloride at room temperature, heat to 60 degrees, break emulsion for 3h, a large number of super particle aggregates appear in the system and are in a clumping state. After washing, dry and crush at 100℃, the product is obviously fibrous and can no longer be used in industrial applications.

[0112] Examples 4-6 and Comparative Examples 4-6

[0113] The coated fluoropolymer particles prepared in Examples 1-3 of this invention and the compounds prepared in Comparative Examples 1-2 were used as flame retardants, and their performance was compared with that of commonly used flame retardants and flame-retardant polymer compositions.

[0114] After the corresponding components were mixed evenly, they were extruded and granulated using a twin-screw extruder. The resulting granules were then injected into standard test strips using an injection molding machine, and finally, standard tests were performed. Polycarbonate (PC) was dried at 120°C for 4 hours before use. The twin-screw extruder used had an aspect ratio of 36 and was equipped with precise temperature control and vacuum degassing equipment. The screw speed was 100-800 rpm, and the extrusion working temperatures were: Zone 1 220°C-250°C, Zone 2 230°C-260°C, Zone 3 230°C-270°C, Zone 4 240°C-280°C, with a residence time of 1-3 minutes. The flame retardant properties of the prepared polymer compositions were characterized. See Table 1, which shows the formulations (parts by weight) and flame retardant test results of the polymer compositions prepared in Examples 4-6 and Comparative Examples 4-6 of this invention.

[0115] Table 1. Formulations and flame retardant test results of the polymer compositions prepared in Examples 4-6 and Comparative Examples 4-6 of this invention.

[0116]

[0117] According to the test results in Table 1, under the same addition amount, the coated fluoropolymer particles of the present invention have better flame retardant effect and can achieve a higher level of flame retardancy without compounding other flame retardants.

[0118] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A coated fluoropolymer, characterized in that, This includes fluoropolymers whose surfaces are completely or partially coated with copolymers containing silicon and sulfur, said coated fluoropolymers being prepared by an emulsion-hydrolysis condensation polymerization method, comprising the following steps: A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c; The silicon compound a includes one or more of the following: compounds containing unsaturated groups and having hydrolyzable groups attached to silicon atoms, their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof; B) Using water or a water-organic solvent as the dispersion medium, a hydrolysis-condensation reaction is carried out on the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b to obtain a reactive emulsion; The silicon compound b includes one or more of the following: compounds having hydrolyzable groups attached to silicon atoms, their hydrolysates, partially hydrolyzed-condensates, and mixtures thereof; C) The reaction emulsion is separated into solid and liquid phases and dried to obtain a coated fluoropolymer; The silicon- and sulfur-containing copolymer is a polymer with a cross-linked structure; The mass ratio of the fluoropolymer to the silicon- and sulfur-containing copolymer in the coated fluoropolymer is 95:5 to 5:

95. The mass fraction of sulfur in the coated fluoropolymer is 0.1-10%.

2. The coated fluoropolymer according to claim 1, characterized in that, Of the silicon compound a and silicon compound b, at least one contains a trifunctional silicon compound and / or a tetrafunctional silicon compound.

3. The coated fluoropolymer according to claim 1, characterized in that, The fluoropolymer is selected from homopolymers, copolymers, or mixtures thereof that contain repeating units derived from one or more fluorinated α-olefin monomers.

4. The coated fluoropolymer according to claim 3, characterized in that, The fluoropolymer is a protofibrous fluoropolymer.

5. The coated fluoropolymer according to claim 4, characterized in that, The unsaturated sulfonate monomers include one or more of sodium styrene sulfonate, potassium styrene sulfonate, sodium allyl sulfonate, potassium allyl sulfonate, sodium vinyl sulfonate, potassium vinyl sulfonate, sodium methyl allyl sulfonate, potassium methyl allyl sulfonate, sodium 3-allyloxy-2-hydroxy-1-propanesulfonate, potassium 3-allyloxy-2-hydroxy-1-propanesulfonate, sodium 2-acrylamido-2-methylpropanesulfonate, and potassium 2-acrylamido-2-methylpropanesulfonate.

6. The coated fluoropolymer according to claim 1, characterized in that, The emulsion polymerization temperature in step A) is 60~90℃, and the emulsion polymerization time in step A) is 1~10 hours.

7. The coated fluoropolymer according to claim 1, characterized in that, The temperature of the hydrolysis-condensation reaction in step B) is 0~90℃, and the time of the hydrolysis-condensation reaction in step B) is 0.1~10 hours.

8. A method for preparing the coated fluoropolymer as described in claim 1, comprising the following steps: A) Using water or a water-organic solvent as the dispersion medium, and silicon compound a and unsaturated sulfonate monomers as comonomers, in the presence of an initiator, emulsion polymerization is carried out to obtain copolymer emulsion c; B) Using water or a water-organic solvent as the dispersion medium, a hydrolysis-condensation reaction is carried out on the fluoropolymer, basic compound, copolymer emulsion c, and optional silicon compound b to obtain a reactive emulsion; C) The reaction emulsion is separated into solid and liquid phases and dried to obtain coated fluoropolymer particles.

9. A polymer composition comprising a polymer matrix and a coated fluoropolymer dispersed in the polymer matrix; The coated fluoropolymer is the coated fluoropolymer according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polymer blends for manufacture, articles obtained from same and use thereof

    CN1125096C

  • Gas turbine with pulsating gas flows

    US3383092A

  • Glass reinforced polyester resins containing polytetrafluoroethylene and flame retardant additives

    US3671487A

  • 0.1% to about 2.0% by weight polytetrafluoroethylene emulsion modified polyethylene terephthalate with improved processing characteristics

    US3723373A

  • Fluorosilicone-containing acrylate copolymer emulsion prepared with reactive emulsifier and method thereof

    CN102516448A